Complications of Volar Plating of Distal Radius Fractures: A Systematic Review - Alter, Todd H.; Sandrowski, Kristin; Gallant, Gregory; Kwok, Moody; Ilyas, Asif M. (Journal of Wrist Surgery, 2019)
Background In recent years, there has been an increased utilization of volar locking plate fixation of distal radius fractures (DRFs). However, reported long-term complication rates with this technique remain unclear.Purpose The purpose of this systematic review was to investigate the pooled incidence of complications associated with volar locking plating of DRF.Methods A search of the Scopus database was performed from 2006 through 2016. Studies were considered eligible if they had a diagnosis of a DRF and were treated with a volar locking plate with an average of 12 months or longer follow-up.Results The literature search yielded 633 citations, with 55 eligible for inclusion in the review (total n = 3,911). An overall complication rate of 15% was identified, with 5% representing major complications requiring reoperation. The most common complication types identified included nerve dysfunction (5.7%), tendon injury (3.5%), and hardware-related issues (1.6%).Conclusion Nerve complications were reportedly higher than tendon and hardware-related complications combined. However, despite varying complication rates in the literature, this systematic review reveals an overall low complication rate associated with volar locking plating of DRF.
Keywords: distal radius fracture; volar locking plate; complications